Recurrent Generalized Urticaria at Insulin Injections Sites - Sackey, A.H. (BMJ, 2000)
In July 1998 a six year old boy with insulin dependent diabetes presented one year after diagnosis with an urticarial rash involving all insulin injection sites. The pruritic rash started 10 minutes after injection of human Mixtard 30 (Novo Nordisk) in the arm. He was otherwise well. The rash occurred at injection sites on the arms, thighs, and buttocks (not used for two months), which disappeared spontaneously within 12 hours. Subsequently in September 1998 (figure), December 1998, and February 1999 he had milder episodes soon after insulin injection. When the insulin was changed to Humulin M3 (Lilly) he had three urticarial reactions in the first two weeks and further reactions in September 1999 and April 2000. The mean insulin dose was 0.61 units/kg/day. There was no history of atopy.
Keywords: Urticaria; insulin injections